Cisternal irrigation and clot removal to prevent vasospasm and poor outcome in aneurysmal subarachnoid hemorrhage: Systematic review and meta-analysis. (June 2022) - Florez-Perdomo, William; Mishra, Rakesh; García-Ballestas, Ezequiel; Lozada-Martínez, Ivan David; Quiñones-Ossa, Gabriel Alexander; Joaquim, Andrei; Agrawal, Amit; Janjua, Tariq; Rahman, Sabrina; Suarez-Causado, Amileth; Moscote-Salazar, Luis Rafael
Abstract: Introduction: Cerebral vasospasm is the most common factor contributing to morbidity and poor outcome in patients with aneurysmal subarachnoid hemorrhage, second only to rebleeding. Most of current evidence assessed the role of vasodilator effect of the irrigating fluid, and the evidence on effects of cisternal irrigation and clots is currently scarce. Method: According to PRISMA guidelines, determined databases were searched for studies and a meta-analysis was performed. Studies included had to meet the established criteria. The statistical analysis was carried out to obtain relative risk with the Mantel-Haenszel methodology for dichotomous variables. Results: After screening and thorough review, five articles were included for qualitative and quantitative synthesis. (n = 621) participants included in this study with n = 472 for the irrigation group and n = 149 for the non-irrigation group. The mean age of the patients was 59.5 years (age range 27–91 years), with 33.5% male and 66.5% female patients. Cisternal irrigation and clot removal reduce vasospasm (OR 0.46; 95% CI 0.22–0.95) and poor outcome (OR 0.41; 95% CI 0.25–0.65). Conclusions: Irrigation of cisterns and aggressive clot removal is a safe and effective procedure in preventing vasospasm and poor outcome in aSAH patients. No significant differences in hemorrhagic, ischemic, and infectious complications with cisternal irrigation and clot removal were reported. Removal of blood clots increases clot clearance and reduces the risk of the development of post-aneurysmal hydrocephalus. Highlights: Cisternal irrigation and clot removal reduce vasospasm and poor outcome in aSAH. Removal of blood clots increase clot clearance and reduces the risk of hydrocephalus. There is a lack of good quality evidence on cisternal irrigation and clot removal in aSAH.